2018
DOI: 10.3389/fmicb.2018.00269
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Plasma MicroRNA-208a as Potential Biomarker of Chronic Indeterminate Phase of Chagas Disease

Abstract: Chagas cardiomyopathy is the most severe clinical manifestation of chronic Chagas disease. The disease affects most of the Latin American countries, being considered one of the leading causes of morbidity and death in the continent. The pathogenesis of Chagas cardiomyopathy is very complex, with mechanisms involving parasite-dependent cytopathy, immune-mediated myocardial damage and neurogenic disturbances. These pathological changes eventually result in cardiac myocyte hypertrophy, arrhythmias, congestive hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 48 publications
0
40
0
2
Order By: Relevance
“…In our study, miR-208a-3p was not detected in most of the serum samples. A previous study reported upregulation of miR-208a-3p in plasma samples from patients with the indeterminate form of Chagas disease [25]. Based on these findings, a larger cohort comparing the expression levels of miR-208a-3p in plasma and serum would be relevant to better define the role of this miR and its value as a circulating biomarker.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In our study, miR-208a-3p was not detected in most of the serum samples. A previous study reported upregulation of miR-208a-3p in plasma samples from patients with the indeterminate form of Chagas disease [25]. Based on these findings, a larger cohort comparing the expression levels of miR-208a-3p in plasma and serum would be relevant to better define the role of this miR and its value as a circulating biomarker.…”
Section: Discussionmentioning
confidence: 81%
“…In Chagas disease, the expression levels of miR-208a and miR-208b were altered in the heart from CCC subjects [24]. Additionally, the potential of miR-208a as a biomarker for Chagas disease has been explored [25]. In the present study, we evaluated the expression profile of circulating microRNAs in three groups: subjects with CCC, subjects with indeterminate form of Chagas disease, and healthy controls, in order to identify possible correlations with clinical parameters associated with the disease prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of people remain in the indeterminate phase for life without any clinical symptoms, but with a positive serology ( Figure 2). Historically, it has not been possible to accurately predict which indeterminate-phase individuals will progress to a chronic disease state; however, a type of circulating plasma microRNA, referred to as microRNA-208a, has been studied as a potential biomarker for predicting the risk of Chagas disease progression (12).…”
Section: Introductionmentioning
confidence: 99%
“…When studying the expression of microRNAs in TECs from infected animals, many of these non-coding RNAs were up- or down-regulated. The bioinformatic-based simulation revealed that various down-regulated miRNAs can result in the up-regulation of biological processes involving ECM proteins, cell adhesion, and cell migration ( 49 ). In keeping with these findings, the expression of cell adhesion and cell migration-related molecules, including chemokines as well as ECM proteins by TEC is enhanced in thymuses from infected mice ( 23 , 42 , 50 , 51 ), as well as after in vitro infection ( 48 ) with functional consequences as further discussed in detail below.…”
Section: The Thymic Microenvironment In T Cruzi Imentioning
confidence: 99%